Canonical and Singular Propagation of Ultrashort Pulses in a Nonlinear Medium - Karl Glasner; Miroslav Kolesik; Jerome V. Moloney; Alan C. Newell (International Journal of Optics)
We examine the two types of singular behaviors of ultrashort pulses in a nonlinear medium, pulse steepening if the weak longitudinal dispersion is normal and collapse if it is anomalous. Connections with analogous behaviors of wave packets of almost monochromatic waves in strongly dispersive media are discussed.